Branched isomeric 1, 2, 3-triazolium-based ionic liquids: new insight into structure–property relationships. Issue 44 (21st October 2015) - Lartey, M.; Meyer-Ilse, J.; Watkins, J. D.; Roth, E. A.; Bowser, S.; Kusuma, V. A.; Damodaran, K.; Zhou, X.; Haranczyk, M.; Albenze, E.; Luebke, D. R.; Hopkinson, D.; et al.
Abstract : Series of branched isomeric 1, 2, 3-triazolium-based ionic liquids (ILs) were synthesized and characterized. The effect of branching on thermal and physical properties is investigated. Abstract : A series of four isomeric 1, 2, 3-triazolium-based ionic liquids (ILs) with vary degree of branching were synthesized and characterized to investigate the effect of ion branching on thermal and physical properties of the resulting IL. It was found that increased branching led to a higher ionicity and higher viscosity. The thermal properties were also altered significantly and spectral changes in the near edge X-ray absorption fine structure (NEXAFS) spectra show that branching affects intermolecular interaction. While the ionicity and viscosity varying linearly with branching, the MDSC and NEXAFS measurements show that the cation shape has a stronger influence on the melting temperature and absorptive properties than the number of branched alkyl substituents.